Analysis of the impact of carbon dissolution and energy transport on the flow in the hearth of an ironmaking blast furnace by transient CFD simulations. (1st March 2023) - Merten, H.; Wirtz, S.; Bartusch, H.; Kaymak, Y.; Hojda, S.; Lin, R.; Scherer, V.
Highlights: Transient simulation of the blast furnace hearth considering the tapping cycles and the periods in-between. Novel approach for modelling the inflow of liquid slag and liquid hot metal. Hot metal density described as a function of temperature and carbon content with an additional transport equation and dissolution model for carbon. Thermal stratification and transient evolution of properties of the tapped liquids obtained. Abstract: In the ironmaking blast furnace, layers of coke, ferrous burden (sinter, pellets, lump ore) and additions are heated by an uprising gas flow. While the layers are descending, the iron ore is reduced and begins to melt. The liquid products slag and hot metal trickle downwards into the hearth, where they prevail as two immiscible phases filling the voids within the coke bed and with the slag floating on top of the hot metal. As the hearth is lined with carbon blocks, which are eroded by the passing hot metal flow, this region has a major impact on the campaign length of the blast furnace. The blast furnace hearth is drained intermittently by opening the taphole and closing it to end the tap. Hence, the fluid phases in the hearth are in a transient state with the liquid levels constantly varying and the flow conditions being determined by the tapping/non-tapping state. In addition, dissolution of carbon into the hot metal and cooling applied to the refractory affect the local hot metal flow. This work presents a CFD-model, which is capable to calculate the multiphase flow in a 3-dimensional hearth at an industrial scale. The tool allows for modelling of the transient transport processes, including multiple tapping cycles by utilizing new approaches for the transition between tapping/non-tapping and the inflow of liquids into the hearth. Furthermore, the dissolution of carbon, energy transport in the liquids and the locally varying density of hot metal depending on temperature and carbon content are included. With this approach, thermal stratification and circulation effects induced by buoyancy can be described over a period of nearly 8 h, thus covering 4 tapping cycles. In addition to an analysis of energy, carbon content and velocity fields, the transient evolution of tapped hot metal properties (temperature, carbon) are obtained and compared to available plant data.